2008
DOI: 10.1093/jnci/djn309
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction for Estrogen Receptor-Positive Breast Cancer Based on Postneoadjuvant Endocrine Therapy Tumor Characteristics

Abstract: BackgroundUnderstanding how tumor response is related to relapse risk would help clinicians make decisions about additional treatment options for patients who have received neoadjuvant endocrine treatment for estrogen receptor–positive (ER+) breast cancer.MethodsTumors from 228 postmenopausal women with confirmed ER+ stage 2 and 3 breast cancers in the P024 neoadjuvant endocrine therapy trial, which compared letrozole and tamoxifen for 4 months before surgery, were analyzed for posttreatment ER status, Ki67 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
477
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(502 citation statements)
references
References 17 publications
15
477
0
10
Order By: Relevance
“…In controlled trials of endocrine therapy for estrogen receptor-positive breast cancer, dynamic changes in Ki-67 expression levels measured 2 weeks after starting therapy, as opposed to static pretreatment Ki-67 expression, were associated with recurrence-free survival [24,35]. Greater reductions in Ki-67 expression with endocrine therapy associated with more benefit.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In controlled trials of endocrine therapy for estrogen receptor-positive breast cancer, dynamic changes in Ki-67 expression levels measured 2 weeks after starting therapy, as opposed to static pretreatment Ki-67 expression, were associated with recurrence-free survival [24,35]. Greater reductions in Ki-67 expression with endocrine therapy associated with more benefit.…”
Section: Discussionmentioning
confidence: 97%
“…Ki-67 protein expression is not used as prognostic or predictive factors in HNSCC because studies evaluating Ki-67 for these purposes have been inconclusive [17][18][19][20][21][22]. However, in breast cancer, Ki-67 expression is significantly associated with a robust tumor response to hormone therapy and anthracycline-based neoadjuvant chemotherapy [23,24]. Further, Ki-67 is a component of two commercial tests for breast cancer recurrence risk that predict efficacy of therapy [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…4 It is noteworthy that Future studies also should focus on neoadjuvant endocrine therapy, especially for luminal A breast cancer. If our study is replicated in this setting, then use of the preoperative endocrine prognostic index (PEPI) score, which has been correlated with patient outcomes, 35 should be preferred to the Sataloff scale. It will also be helpful in future studies to compare PET parameters with other factors, such as gene expression signatures (Oncotype DX; Genomic Health Inc., Redwood City, Calif).…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase expression by breast cancer cells has been shown to influence the effectiveness of endocrine treatments for breast cancer (8,9). Ellis et al (10) conducted a study using a sample from a clinical trial comparing tamoxifen and letrozole as neoadjuvant endocrine therapies, and found that aromatase expression levels in tumor and somatic cells was correlated with treatment-induced changes in Ki-67, RFS, and breast cancer-specific survival (BCSS) (11)(12)(13).…”
Section: Literature Searchmentioning
confidence: 99%